Mewirausahakan Birokrasi Sekolah Tinggi Penerbangan Indonesia Dengan Pola Pengelolaan Keuangan Badan Layanan Umum - Tiarto Tiarto (Research and Development Agency of The Ministry of Transportation, 2011)
Currently, the STPI is in stagnant condition or status quo to be a Public Service Agency. This paper is intended for those who feel disturbed by this fact, and have concern for the STPI.Some problems: achievement cadets who decline, low quality but the quantity of excess human resources, education systems, curricula, low reward / low salaries, expenditures per student is high, crowded dormitories, degree requirements, marketing graduates, competency standards / certification, accreditation, Research and Community Service (PPM) which does not fit with the mission, training co-operation contracts with third parties, outsourcing and so on.It all resulted in efficiency, effectiveness, productivity and low yields, thus the need for reform toward a more entrepreneurial way STPI bureaucracy, and fortunately with a strong new leadership of the Chairman with the spirit of high entrepreneur, STPI want to build a center for human flight (center of excellence human resources development for aviation), including the urgent need to change the status of a Pattern of Financial Management of Public Service Agency.